Clinical results of fibroblast activation protein (FAP) specific PET for non-malignant indications: systematic review - Windisch, Paul; Zwahlen, Daniel R.; Giesel, Frederik L.; Scholz, Eberhard P.; Lugenbiel, Patrick; Debus, Jürgen; Haberkorn, Uwe; Adeberg, Sebastian (EJNMMI Research, 2021)
Small molecules targeting fibroblast activation protein (FAP) have emerged as a new group of tracers for positron emission tomography (PET) in 2018. While most of the existing literature has been focussed on the application of FAP-specific PET in various kinds of cancers, some researchers have, both intentionally or unintentionally, used FAP-specific PET in patients with non-cancerous diseases. The purpose of this systematic review is therefore to summarize the available evidence of FAP-specific PET for non-malignant indications.
Gesehen am 07.04.2021